2019
DOI: 10.1007/s41669-019-0132-5
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden and Health-Related Quality of Life Associated with Current Treatments for Anaemia in Patients with CKD not on Dialysis: A Systematic Review

Abstract: BackgroundThe cost and health-related quality of life (HRQoL) burden associated with treatments for anaemia of chronic kidney disease (CKD) is not well characterized among non-dialysis-dependent (NDD) patients.ObjectiveOur objective was to review the literature on costs and HRQoL associated with current treatments for anaemia of CKD among NDD patients.MethodsThe Cochrane Library, MEDLINE, Embase, NHS EED, and NHS HTA databases were searched for original studies published in English between 1 January 2000 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
0
14
0
1
Order By: Relevance
“…Anemia of chronic kidney disease (CKD) is associated with increased risk of cardiovascular events and mortality, increased healthcare resource utilization (HCRU), and reduced health-related quality of life (HRQoL) [ 1 6 ]. While the prevalence of anemia increases with CKD severity [ 7 9 ], anemia also imparts a substantial healthcare burden in early-stage CKD [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anemia of chronic kidney disease (CKD) is associated with increased risk of cardiovascular events and mortality, increased healthcare resource utilization (HCRU), and reduced health-related quality of life (HRQoL) [ 1 6 ]. While the prevalence of anemia increases with CKD severity [ 7 9 ], anemia also imparts a substantial healthcare burden in early-stage CKD [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Marked reduction in ESA use has resulted in a shift towards less intensive therapy and lower Hb treatment targets in patients with anemia of CKD [ 8 , 20 , 21 ]. Notably, many patients with CKD not on dialysis do not receive any anemia treatment [ 7 , 22 ], despite some evidence that untreated versus treated anemia is associated with higher HCRU and decreased HRQoL [ 5 , 6 ]. Moreover, treating anemia of CKD can reduce the requirement for RBC transfusions, and thus associated risks from transfusion-related reactions and the development of alloantibodies [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin values which define anemia are determined by the World Health Organization (WHO) and are different for males, females, and children [1]. The classic symptoms of anemia-fatigue, dizziness or lightheadedness, headache, shortness of breath, and difficulty concentrating-can lead to major social and economic consequences such as lost wages and medical care [2,3] contingent on this common co-morbidity. Severe anemia is often a sequela of malnutrition, parasitic infections or underlying disease and is a significant risk factor for morbidity and mortality, especially in vulnerable populations such as children, the elderly and the chronically ill [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…HRQoL provides a comprehensive appraisal of disease burden, incorporating assessment of symptoms, functional capacity, and well-being related to an effective treatment. A recent systematic review [ 9 ] showed that treatment of anemia comparing with untreated anemia among patients with CKD was associated improvement of HROoL. However, the aimed of higher hemoglobin level may not be necessary, which has a connection with a certain outcome of HROoL improvement.…”
Section: Introductionmentioning
confidence: 99%